The Expansion of the Fibre Optic Network in Germany: Switching the Lights to Green - Cordelius Ilgmann (Wirtschaftsdienst)
Abstract The coalition agreement of the new German government meets many of the demands previously made by practitioners at the state and local level. For the first time, the ruling parties have committed to an infrastructure objective. The federal government thereby implements a strategic decision that states like Schleswig-Holstein and Thuringia have made before: the basis for a sustainable digital infrastructure is a comprehensive optic fibre network to the building/home (FTTB/FTTH). As to state subsidies, the so-called “Betreibermodell” offers an efficient policy alternative to the current predominantly used system of state subsidies. However, private interest is trying to undermine this change in policy at the implementation level.